Assessing the Impact of Political Scandals on Attitudes toward Democracy: Evidence from Canada's Sponsorship Scandal. Issue 4 (22nd February 2016) - Ruderman, Nick; Nevitte, Neil
Abstract: Satisfaction with the workings of democracy seems to have declined in Canada, as it has in other established democracies. Political scandals are one frequently invoked explanation for that shift. But there is substantial scholarly disagreement about whether political scandals undermine democratic satisfaction. This paper uses evidence from a conveniently timed round of the CES (Canadian Election Study) from 2004, as well as the CES panel from 2004 and 2006, to explore this relationship more definitively than is usually possible. The results indicate that the scandal eroded satisfaction with the way democracy works but did not undermine support for democracy more generally. Résumé: La satisfaction envers le fonctionnement de la démocratie semble avoir diminué au Canada similairement à ce qu'on observe dans d'autres démocraties établies. Les scandales politiques sont souvent une explication invoquée pour justifier cette situation. Mais il existe un désaccord scientifique substantiel quant à savoir si les scandales politiques sont la cause directe d'une baisse de la satisfaction démocratique. Ce document utilise des questions de l'ÉÉC (Étude électorale canadienne), posées à un moment opportun en 2004, ainsi que la section panel de l'ÉÉC de 2004 à 2006, afin d'explorer directement la relation entre satisfaction démocratique et scandales. Les résultats indiquent que le scandale a effectivement érodé la satisfaction envers le fonctionnement de la démocratie, mais n'a pas semblé affecter le soutien pour les principes démocratiques de base.